RESEARCH WORK AS THE FOUNDATION FOR TRAINING FUTURE SPECIALISTS - Ermekbaeva A. U.; Jaybergenova J. B. (Web of Journals Publishing, 2025)
The article analyzes the role of research activities in the preparation of future researchers and the ability of a specialist to research activities. Research activity, being one of the most important areas of functioning of a modern medical university, creates the basis for effective innovation and requires great attention in the training of future medical researchers.
Keywords: Youth competitiveness, creativity, independence, research activity.